2017
DOI: 10.1002/jcb.26237
|View full text |Cite
|
Sign up to set email alerts
|

Activated proline‐rich tyrosine kinase 2 regulates meiotic spindle assembly in the mouse oocyte

Abstract: Proline-rich tyrosine kinase 2 (PYK2), a member of the protein tyrosine kinase family, plays an important role in various cellular processes. PYK2 can be phosphorylated on tyrosine 402 by diverse stimuli at the cell surface, and recent studies have shown that this activated form of PYK2 is enriched in oocytes and required for fertilization. However, the subcellular localization and functions of activated PYK2 in oocytes remain elusive.In this study, we demonstrate that the localization of p-PYK2 undergoes dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
5
3
Order By: Relevance
“…However, for Ptk2b −/− mice, the number of matured oocytes was 191 oocytes from nine (over 21 oocytes per mice). After (Figure 3l-n), which was different with the previous in vitro results that the spindle assembly was disrupted when PTK2B was inhibited by its inhibitor (Meng et al, 2018).…”
Section: Ptk2b Ablation Improves the Female Fecundity Through Regulcontrasting
confidence: 97%
See 3 more Smart Citations
“…However, for Ptk2b −/− mice, the number of matured oocytes was 191 oocytes from nine (over 21 oocytes per mice). After (Figure 3l-n), which was different with the previous in vitro results that the spindle assembly was disrupted when PTK2B was inhibited by its inhibitor (Meng et al, 2018).…”
Section: Ptk2b Ablation Improves the Female Fecundity Through Regulcontrasting
confidence: 97%
“…Recently, it has been reported that PTK2B was localized to tubulin and its inhibition affects the spindle assembly and oocyte maturation in vitro (Meng et al, 2018). The expression pattern of Ptk2b during germ cell development also suggested that this gene might be crucial in mice fertility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…May function as a component of the microtubule‐organizing center to regulate spindle assembly during the meiotic process of mouse oocytes (Meng et al, ),…”
Section: A Brief History Of Earlier Studies Of Aneuploidy and Admentioning
confidence: 99%